Washback Effect of Vocational High School Final Examination: Indonesian EFL Teachers’ and Students’ Voices - Wensi Alka; Junaidi Mistar; Muhammad Hamdan Fakhrudin (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The English final examination is no longer a high-stake test since National Examination (NE) was abolished in 2021 and replaced with the Ujian Satuan Pendidikan (USP). Therefore, this study explores the washback effects experienced by Indonesian EFL teachers and students and discovers teachers’ and students’ perceptions of the implementation of USP. Six participants, three Indonesian English Foreign Language (EFL) teachers, and three Public Vocational High School students in Singosari were interviewed to meet the research goals. The findings indicated that focusing on teaching to the test, cheating, and feelings and attitudes were the washback effects of the English final examination in implementing USP. Then, the English final examination still harms the teaching and learning process and teachers’ and students’ feelings and attitudes, even though it is not a high-stake test. Besides, the implementation of USP also reduces the washback effect of the English final examination. Keywords: Washback effect, final examination, teachers’ and students’ voices